Stress and Drug-Cue-Induced Craving in Opioid-Dependent Individuals in Naltrexone Treatment - Hyman, Scott M. (2007)
BACKGROUND: Naltrexone is a nonaddictive medication that blocks the euphoric effects of opioids. However, naltrexone treatment is associated with high rates of noncompliance and opioid relapse, possibly because it does not reduce stress and protracted withdrawal symptoms during early recovery. Prior clinical and preclinical research has indicated that both stress and drug-cue-related arousal response is associated with craving and vulnerability to relapse in a range of drug-using populations. AIMS: To examine opioid craving and the subjective and cardiovascular response to stress and drug cues in naltrexone-treated opioid abusers. METHOD: Eleven men and three women engaged in naltrexone treatment for opioid dependence. They were exposed to personalized stress, drug-cue, and neutral-relaxing imagery in a single laboratory session. Subjective (craving, emotion) and cardiovascular (heart rate, systolic blood pressure, and diastolic blood pressure) measures were assessed. RESULTS: Stress and drug-cue-related imagery significantly increased opioid craving, anxiety, and negative emotions and significantly decreased positive emotions compared to neutral imagery. Selective emotional responses were greater in the stress condition than in the drug-cue condition. Only stress-related imagery was associated with an increased cardiovascular response. CONCLUSIONS: Naltrexone-treated opioid abusers demonstrate vulnerability to stress and drug-cue-induced craving and arousal responses that may contribute to the high rates of noncompliance and relapse among opioid-dependent individuals undergoing naltrexone treatment. Pharmacological and behavioral interventions that specifically target the negative affectivity that co-occurs with drug-cue and stress-induced craving could be of benefit in improving naltrexone treatment outcomes in opioid dependence.